Prototypes in architecture. Online discussion (project baikal, 2021)
Avant-garde and modernism have shown that generation of unprecedented and new forms is practically impossible without basing on prototypes. The article considers the “denying of prototypes” declared by architects in different periods of time and its hidden grounds. The mobility of prototypes and their connection with the culture and contexts is discussed.
Keywords: architecture; prototype; design; eclecticism; avant-garde; modernism; parametric architecture